2015
DOI: 10.1123/pes.2014-0139
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the Neighborhood Environment and Children’s Afterschool Moderate-to-Vigorous Physical Activity

Abstract: Previous research suggests the neighborhood environment may be an important influence on children’s physical activity (PA) behaviors; however, findings are inconsistent. The purpose of this study was to further understand the relationship between perceptions of the neighborhood environment and children’s afterschool moderate-to-vigorous PA (MVPA). Utilizing a structural equation modeling technique, we tested a conceptual model linking parent and child perceptions of the neighborhood environment, parent support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 56 publications
2
8
0
Order By: Relevance
“…Associations of low magnitude were observed between time spent outside and child-reported “active parents” and “intangible parental support” confirming findings from a study conducted in the US that parental support was associated with child outdoor PA [17]. Interestingly, all derived factors relating to friend support were significantly associated with time spent outside, with “general friend support” having the highest association observed in our study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Associations of low magnitude were observed between time spent outside and child-reported “active parents” and “intangible parental support” confirming findings from a study conducted in the US that parental support was associated with child outdoor PA [17]. Interestingly, all derived factors relating to friend support were significantly associated with time spent outside, with “general friend support” having the highest association observed in our study.…”
Section: Discussionsupporting
confidence: 86%
“…Studies have also examined parental effects on children's time spent outside. Social support by parents [ 17 ] and parental encouragement [ 18 ] have been found to be associated with time spent outside. A limitation of these studies is that they did not examine the association between friends' influences on time spent outside.…”
Section: Introductionmentioning
confidence: 99%
“…The study quality was rated high in 11 [27,48,56,57,58,63,64,65,66,67,69] and fair in 10 [5,23,26,55,59,60,61,62,68,70] studies. The more detailed quality assessment for each study is presented in the Supplementary material Table S3.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies used parental report questionnaires. Two studies [57,65] measured children’s self-reported outdoor play via questionnaires, while only one study measured outdoor play by using both self and proxy reports [48]. Moreover, outdoor play was measured by focusing on different aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Three items were used to assess parent’s perception of their child’s neighborhood safety; these items were validated in a previous study 28 and more information has been previously published. 30 Additionally, parents reported the number of sports/physically active lessons in the past year that the child participated in and the number of screen devices (i.e., TV, computer, game console) in the child’s bedroom. A 14-item home physical activity resource checklist adopted from a previous study 29 was used to provide information about number of physical activity resources at home or in the yard.…”
Section: Methodsmentioning
confidence: 99%